2012
DOI: 10.1111/j.1476-5381.2012.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the paracrine/autocrine mediator endothelin‐1 in regulation of cardiac contractility and growth

Abstract: Endothelin-1 (ET-1) is a critical autocrine and paracrine regulator of cardiac physiology and pathology. Produced locally within the myocardium in response to diverse mechanical and neurohormonal stimuli, ET-1 acutely modulates cardiac contractility. During pathological cardiovascular conditions such as ischaemia, left ventricular hypertrophy and heart failure, myocyte expression and activity of the entire ET-1 system is enhanced, allowing the peptide to both initiate and maintain maladaptive cellular response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 282 publications
(388 reference statements)
1
79
1
1
Order By: Relevance
“…Ang II, insulin, lipopolysaccharide (LPS), and hydrogen peroxide (H 2 O 2 ) were used to mimic these settings as described elsewhere [10, 2224]. The effects of pro-hypertrophic factors, ET-1 [25] and TGFβ1 [26] on release of exosomes from neonatal CFs were also studied. We measured the total amount of proteins (concentrations), the activity of acetylcholinesterase (AChE), an exosome specific enzyme [27] and protein expression levels of TSG101 and CD63, two exosome markers [5, 6] in total exosomes released from the same number of CFs after the treatment as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Ang II, insulin, lipopolysaccharide (LPS), and hydrogen peroxide (H 2 O 2 ) were used to mimic these settings as described elsewhere [10, 2224]. The effects of pro-hypertrophic factors, ET-1 [25] and TGFβ1 [26] on release of exosomes from neonatal CFs were also studied. We measured the total amount of proteins (concentrations), the activity of acetylcholinesterase (AChE), an exosome specific enzyme [27] and protein expression levels of TSG101 and CD63, two exosome markers [5, 6] in total exosomes released from the same number of CFs after the treatment as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…We found that SERCA mRNA abundance was decreased to a greater extent in hearts from RhoA fl/fl -Cre mice than in those from control mice (Figure 2C), suggesting a greater decrease in cardiac function and contractility (30). Next, we measured effects on calcium transient in individual cardiomyocytes left unstimulated or stimulated with endothelin-1 (ET-1), a neurohumoral agonist that mimics chronic stress in the heart (31). Basal and stimulated calcium transients were significantly lower in RhoA fl/fl -Cre cardiomyocytes than in control cells (Figure 2C), suggesting that RhoA might be involved in mediating increased calcium cycling in response to cardiac stress.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the IP 3 R-2 was thought to be the predominant isoform expressed in the heart. Consequently, most of the studies that focus on the role of IP 3 R in the heart have focused solely on IP 3 R-2 function [13, 33]. However, global genetic knockout of the IP 3 R-2 in mice does not cause any significant difference in the hypertrophic response in pressure overload or dilated cardiomyopathy mouse models [17].…”
Section: Discussionmentioning
confidence: 99%